Insights into German polar research during POLARSTUNDE - A. M. Zuhr; A. M. Zuhr; E. Loebel; E. Loebel; M. Muchow; M. Muchow; D. Dennis; D. Dennis; L. von Albedyll; L. von Albedyll; F. Kruse; H. Kassens; et al. (Polarforschung, 2023)
Polar research is an interdisciplinary and multi-faceted field of research ranging from history to geology and geophysics to social sciences and education. Thus, several different universities and institutions within Germany participate in polar research. The seminar series POLARSTUNDE, organized by the German Society for Polar Research (Deutsche Gesellschaft für Polarforschung) and the German National Committee of the Association of Polar Early Career Scientists (APECS Germany) regularly features different topics of German polar research. Although initially a “pandemic solution”, the seminar series has established itself as a valuable and highly successful part of the German polar research landscape. The seminar series was held in German and was aimed at both scientists and the general public. This article addresses the first season of POLARSTUNDE and provides (1) comprehensive summaries of the talks and (2) insight into the planning and execution from an organizational point of view.